Temporal Preparation, Impulsivity and Short-Term Memory in Depression - Hsu, Tzu-Yu; Lee, Hsin-Chien; Lane, Timothy Joseph; Missal, Marcus (Frontiers in Behavioral Neuroscience, 2019)
Patient suffering of Major Depressive Disorder (MDD) often complain that subjective time seems to ‘drag’ with respect to physical time. This may point towards a generalized dysfunction of temporal processing in MDD. In the present study, we investigated temporal preparation in MDD. “Temporal preparation” refers to an increased readiness to act before an expected event; consequently, reaction time should be reduced. MDD patients and age-matched controls were required to make a saccadic eye movement between a central and an eccentric visual target after a variable duration preparatory period. We found that MDD patients produced a larger number of premature saccades, saccades initiated prior to the appearance of the expected stimulus. These saccades were not temporally controlled; instead, they seemed to reflect reduced inhibitory control causing oculomotor impulsivity. In contrast, the latency of visually-guided saccades was strongly influenced by temporal preparation in controls; significantly less so, in MDD patients. This observed reduced temporal preparation in MDD was associated with a faster decay of short-term temporal memory. Moreover, in patients producing a lot of premature responses, temporal preparation to early imperative stimuli was increased. In conclusion, reduced temporal preparation and short-term temporal memory in the oculomotor domain supports the hypothesis that temporal processing was altered in MDD patients. Moreover, oculomotor impulsivity interacted with temporal preparation. These observed deficits could reflect other underlying aspects of abnormal time experience in MDD.